The solidification of encapsulated jasmine extract using electrostatic atomizer (electrospray) - Rahmam, Syuhaidah; Naim, Mohd Nazli; Mokhtar, Mohd Noriznan; Abu Bakar, Noor Fitrah (Faculty of Engineering, Universiti Putra Malaysia, 2016)
In this work, a non-thermal solidified method of Jasmine extract was developed via the electrostatic atomizer or electrospray technique. The electrospray technique is dependent on two continuous processes which are water evaporation and droplet fission. To verify the water evaporation rates of the atomized droplets, the deposition trajectory distance were varied from 10 to 30 cm. The morphology and size distribution of the deposits were observed and analyzed. From the experimental results, it was noticed that the evaporation rates of the atomized droplets reduced from 2.65 x 10-10 - 1.1 x 10-10 g/s as the trajectory distances of the atomized droplet increased from 10-30 cm. Meanwhile, the droplet fission is increased from 12.5 to 16 disintegrations as the distance went further. The morphology and particles size of the solidified compound were analyzed by SEM and ImageJ software respectively.